Caring for the Vulnerable Geriatric Individual in a Disaster. Issue Volume 34:Issue s1(2019) (May 2019) - Mace, Sharon; Doyle, Connie
Abstract : Introduction: The elderly have the highest rates of morbidity/mortality in a disaster and are therefore the most vulnerable. 50% of deaths in Hurricane Katrina were ≥75 years old. In the California wildfires, most deaths were people in their 70s and 80s living in areas with unreliable communication services (without cell phone service, etc.), and were uninformed of the disaster or unable and/or unwilling to evacuate. Issues include social isolation and limited technology skills (may not receive messages). Methods: A review of the literature and after action reports from multiple disasters. Results: Augmented services are needed for persons with decreased mobility (impaired access to transportation and shelters); impaired senses; dependence on devices/technology, comorbidities requiring medications/equipment/oxygen, special feedings, sanitary/hygiene needs increased susceptibility to environmental extremes (heat, cold), inability to do ADLs (need for caregivers), increased susceptibility and increased morbidity/mortality with infections, illnesses, trauma; exacerbation of underlying conditions/illnesses when in crowded transportation vehicles and shelters. Additional stress may precipitate or exacerbate coping skills especially in those with dementia, delirium, or mental health illnesses. Discussion: Recommendations include the following: 1. Communications: messages in various forms: closed captioning, TTY deaf phones, use of family, friends, neighbors, officials for notification in addition to mass communication notices, house-to-house notification. 2. Medical: Medical/Special Needs Shelters to provide medical care (dialysis, etc.), cache of common medications (diabetic and BP medications) and devices (BP monitoring, glucometers), oxygen, wound care supplies, potable and non-potable water, special diets/formulas, feeding tubes, catheter care, diapers and other hygiene supplies. 3. Independence: Health care professionals to assist with medical and psychiatric needs. Caregivers to assist with ADLs. 4. Supervision: Those with dementia, delirium, mental health conditions may need supervision. 5. Transportation: Need for ambulances, wheelchair vans, specially equipped buses/vans in addition to "usual" school buses/vans with access to water, food, and sanitation if traveling long distances.